Conductivity Dispersion Characteristic of Cement Slurry during Early Hydration - Syahrir Ridha , Syahrir (2011)
Electrical conductivity has been increasingly used for material characterization in the form of dispersion characteristic. However, the application of this method to the cement slurry is limited. This paper investigates the influence of water to cement ratio and degree of hydration to the dispersion characteristic of cement slurry during 24 hrs of hydration. The magnitude and frequency effect are used to describe the conductivity dispersion characteristic. It is observed that the magnitude of conductivity dispersion increases with the reduction in water content and pore volume. During initial hydration, the dispersion characteristic appears in the minimum value and raises as hydration continue. The frequency effect is growth as the hydration and saline concentration increases. It is implied that the single frequency measurement for evaluating the cement slurries properties may not be reliable. An implicit correlation to the interface conductivity is indicated from dispersion respond throughout hydration process.